Energy efficient concrete with n-octadecane/xGnP SSPCM for energy conservation in infrastructure. (1st March 2016) - Jeong, Su-Gwang; Chang, Seong Jin; Wi, Seunghwan; Kang, Yujin; Lim, Jae-Han; Chang, Jae D.; Kim, Sumin
Highlights: SSPCM brought high heat storage property and high enthalpy accumulation of concrete. Peak temperature reduction and time lag effect was confirmed through dynamic heat transfer analysis. SSPCM concrete has high thermal conductivity in comparison with general concrete. SSPCM concrete can be applied to various sectors in building for reducing heating and cooling load. Abstract: Among the preparation methods of shape-stabilized PCMs (SSPCMs), incorporation of a PCM into construction materials has been proposed as a passive means of decreasing the overall heating and cooling demand of a building. PCMs can be incorporated in a variety of construction materials, such as gypsum plaster boards, concrete and plaster. In this study, we prepared concrete with a high heat storage property by using n-octadecane based SSPCM for application to building. The prepared SSPCM was applied to the concrete as a fine aggregate because its shape is grain type. Then we prepared the SSPCM concrete by compositing SSPCM to concrete. The physical property of SSPCM concrete was analyzed density analysis. And thermal properties of the SSPCM concrete were analyzed by differential scanning calorimeter (DSC), enthalpy analysis and thermogravimetric analysis (TGA). Finally, we carried out dynamic heat transfer analysis of the SSPCM concrete for evaluation of peak temperature reduction time lag effect of the prepared samples. From this research, we confirmed the high thermal properties and possibility to apply SSPCM concrete to heat storage structures and various other fields. We expect SSPCM concrete would be useful in heat storage building materials and to establish a heat storage structure for enhancing thermal efficiency.